ADMINISTERING CLASSES IN VIRTUAL LEARNING ENVIRONMENT: FACILITATIONS, PRINCIPLES, EDUCATORS’ ROLES AND INTERACTIONS - Nur Afni Mahiya Usemahu; Yulia Fernandita (Universitas Islam Negeri Alauddin Makassar, 2021)
This study investigates teachers’ competencies in the implementation of facilities, principles, educators’ roles, and interactions in the Virtual Learning Environment (VLE). Using explanatory sequential mixed method, it aims to examine whether all those competencies such as learning system tools and resources, technology quality, and workload management are considered throughout the learning process. In total, 102 students from the Faculty of Tarbiyah and Teachers’ Training at Antasari State Islamic University were involved in the survey. Fourteen of them, as well as three lecturers, were then interviewed. The results indicate that despite students’ limited access to the internet, lecturers attempt to provide all students’ facilities. However, in some departments, various learning activities, monitoring, and feedback still need to be improved. The lecturers generally execute the principle of the virtual learning environment. The students mostly believe that lecturers are aware of their roles, and manage their interactions well. In conclusion, the study suggests teachers’ competencies in the virtual learning environment and calls for further studies in this subject.